Analisis Pengalaman Operator Mesin Terhadap Dampak Kebisingan dan Kelelahan Kerja Di PT. PP London Sumatra Indonesia, Tbk Dolok POM - Nurhayati, Nurhayati; Indah Syahputri, Nayla; Harahap, Mufidah; Alvionita, Elsti; Gajah, Herliana; Siregar, Izdhihar Rozananti (JUKEJ : Jurnal Kesehatan Jompa, 2025)
Noise is one of the physical hazards frequently encountered in industrial environments, especially in production processes involving intensive machine use. Exposure to noise exceeding the threshold can cause hearing loss and work fatigue. This study aims to analyze the experiences of machine operators related to the impact of noise and work fatigue at PT. PP London Sumatra Indonesia, Tbk Dolok POM. The method used in this study is qualitative with a phenomenological approach, involving six machine operators in the kernel station and engine room areas who work an average of 7.5 hours per day. Data were collected through interviews, observations, and documentation, then analyzed thematically. The results showed that the noise level in the work area ranged from 86–89 dBA, which exceeds the Threshold Limit Value of 85 dBA. All operators (100%) reported experiencing physical and mental fatigue characterized by impaired concentration, difficulty sleeping, and work stress. The use of personal protective equipment such as earplugs and earmuffs is still low due to reasons of discomfort and difficulty in communicating. High noise has been shown to have a significant influence on increasing work fatigue and decreasing productivity. This study concluded that excessive noise exposure triggers work fatigue in machine operators, so that supervision of PPE use, job rotation, and more effective control of the work environment are needed.